Measurement of bone mineral density in stable COPD patients using ultrasound densitometry: prevention is better than cure - Ali, M. Arif; Salve, Vijay Tukaram (International Journal Of Community Medicine And Public Health, 2017)
Background: COPD is a multisystem disorder and three or more comorbidities are associated with poor prognosis. Osteoporosis is one of the major comorbidity and is associated with an impact on the primary dysfunction in COPD. Bone Mineral density measures strength of the skeletal system and ultrasound based BMD measurement is a cheap, cost effective intervention which is also free from ionizing radiation. Ultrasound densitometer BMD measurement can be utilized for screening of osteoporosis in COPD patients. Methods: 50 stable COPD (diagnosed as per GOLD guideline) patients attending a post graduate institute in Mumbai were enrolled for the study and bone mineral density was measured using ultrasonography BMD scan of calcaneum. Results: Among 50 enrolled COPD patients, 27 (54%) patients had osteopenia and 14 (28%) were osteoporotic.9 (64.3%) female and 18 (50%) male COPD patients had osteopenia. 4 (28.6%) females and 10 (27.8%) males were osteoporotic. Conclusions: Considering the additional burden of osteoporosis on management of COPD, it is advisable to measure BMD to formulate strategies to prevent fractures in COPD patients.